DEHYDRATION PROCESS AND STRUCTURAL DEVELOPMENT OF CORDIERITE CERAMIC PRECURSORS DERIVED FROM FTIR SPECTROSCOPIC INVESTIGATIONS - Voll D.; Beran A. (My University, 2002)
Cordierite precursors were prepared by a sol-gel process using tetraethoxysilane, aluminum sec.-butoxide, and Mg metal flakes as starting materials. The precursors were treated by 15-h heating steps in intervals of 100 °C from 200 to 900 °C; they show a continuous decrease in the analytical water content with increasing preheating temperatures. The presence of H2O and (Si,Al)–OH combination modes in the FTIR powder spectra prove the presence of both H2O molecules and OH groups as structural components, with invariable OH concentrations up to preheating temperatures of 500 °C. The deconvolution of the absorptions in the (H2O,OH)-stretching vibrational region into four bands centred at 3584, 3415, 3216 and 3047 cm−1 reveals non-bridging and bridging H2O molecules and OH groups. The precursor powders remain X-ray amorphous up to preheating temperatures of 800 °C. Above this temperature the precursors crystallize to μ-cordierite; at 1000 °C the structure transforms to α-cordierite. Close similarities exist in the pattern of the 1400–400 cm−1 lattice vibrational region for precursors preheated up to 600 °C. Striking differences are evident at preheating temperatures of 800 °C, where the spectrum of the precursor powder corresponds to that of conventional cordierite glass. Bands centred in the “as-prepared” precursor at 1137 and 1020 cm−1 are assigned to Si–O-stretching vibrations. A weak absorption at 872 cm−1 is assigned to stretching modes of AlO4 tetrahedral units and the same assignment holds for a band at 783 cm−1 which appears in precursors preheated at 600 °C. With increasing temperatures, these bands show a significant shift to higher wavenumbers and the Al–O stretching modes display a strong increase in their intensities. (Si,Al)–O–(Si,Al)-bending modes occur at 710 cm−1 and the band at 572 cm−1 is assigned to stretching vibrations of AlO6 octahedral units. A strong band around 440 cm−1 is essentially attributed to Mg–O-stretching vibrations. The strongly increasing intensity of the 872 and 783 cm−1 bands demonstrates a clear preference of Al for a fourfold-coordinated structural position in the precursors preheated at high temperatures. The observed band shift is a strong indication for increasing tetrahedral network condensation along with changes in the Si–O and Al–O distances to tetrahedra dimensions similar to those occurring in crystalline cordierite. These structural changes are correlated to the dehydration process starting essentially above 500 °C, clearly demonstrating the inhibiting role of H2O molecules and especially of OH groups.